Legal politics as a catalyst in forming sharia economic legal system in the Indonesia’s new order and reform era - andi fariana (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
The formation of the National Legal System is governed by legal raw materials prevailing in society (living law), including the Customary, Islamic, and Western Laws. As part of the living law, Islamic Law affects the National Legal System, especially in sharia economic law, in line with sharia economic growth in various sectors. In forming a sharia economic legal system, legal politics is significant as a catalyst that reflects the ongoing leadership pattern. This normative legal research aimed at explaining the important role of legal politics as a catalyst in forming the Sharia Economic Legal System in Indonesia, by using statute and historical approaches. The study found that various legal products at the end of the new order and the reform era indicated the existence of democratic legal politics and supported the formation of the sharia economic legal system. However, contradictions and obstacles existed, and more sharia economic law products were still needed. Therefore, a positive legal political atmosphere must be maintained by the participation of the community and religious leaders, as legal politics is strongly influenced by powers or concerns, and there will be always rejection and acceptance in the development of the sharia economic legal system due to various interests.